Heartbeat Biometrics for Remote Authentication Using Sensor Embedded Computing Devices - Md Saiful Islam (International Journal of Distributed Sensor Networks)
Biometric verification has been included in remote user authentication schemes recently. In this paper, we have proposed the use of heartbeat biometrics for its liveness property as a possible defense against spoof attacks in remote authentication. Sensor embedded mobile computing devices such as smart phones could be used to capture biometric signals and to replace the use of traditional smart cards. For the remote authentication, we have adopted the state-of-the-art scheme. We have described the biometric verification method instead of using cryptographic hash function for feature matching. We have used the piecewise aligned morphology (PAM) of heartbeat signal as a biometric feature. The biometric verification method was tested with ECG records of 100 individuals and 1.34% of equal error rate (EER) was obtained. This feature could be computed and transmitted efficiently using mobile computing devices. The proposed scheme offers more security and convenience to users. Additionally, it becomes robust against noisy biometric input. The proposed scheme should be feasible for remote authentication using sensor embedded computing devices in many practical applications such as remote healthcare.